Do Two or More Multicomponent Instruments Measure the Same Construct? Testing Construct Congruence Using Latent Variable Modeling. (October 2016) - Raykov, Tenko; Marcoulides, George A.; Tong, Bing
A latent variable modeling procedure is discussed that can be used to test if two or more homogeneous multicomponent instruments with distinct components are measuring the same underlying construct. The method is widely applicable in scale construction and development research and can also be of special interest in construct validation studies. The approach can be readily utilized in empirical settings with observed measure nonnormality and/or incomplete data sets. The procedure is based on testing model nesting restrictions, and it can be similarly employed to examine the collapsibility of latent variables evaluated by multidimensional measuring instruments. The outlined method is illustrated with two data examples.